The diversity of chemical compounds of bilih fish body (Mystacoleucus padangensis) originating from Lake Toba and Lake Singkarak, Sumatra, Indonesia - ABDUL RAZAK (Biodiversitas Journal of Biological Diversity, 2018)
Razak A. 2018. The diversity of chemical compounds of bilih fish body (Mystacoleucus padangensis Bleeker) originating from Lake Toba and Lake Singkarak, Sumatra, Indonesia. Biodiversitas 19: 1552-1557. Bilih fish (Mystacoleucus padangensis) is an endemic fish in Lake Singkarak, West Sumatra. Bilih fish in Lake Singkarak experiencing pressure due to human activities that destroy the habitat of this fish in Lake Singkarak. The improvement of bilih fish habitat conducted by the government by introducing bilih fish to Lake Toba for bilih fish preservation. The purpose of this study is to describe the diversity of chemical compounds and their relation to several ecological factors that influence bilih fish in Lake Toba and Lake Singkarak. The research method is survey method. Bilih fish taken at three to four points on both Lakes. The distance between sample points is 8000 m. The result of this research is to find the morphology of bilih fish from Lake Toba bigger than bilih Lake Singkarak fish. The bilih fish Fins of Lake Toba have a 52.08% CaO compound (per 100 ppm sample), the fins of Lake Singkarak have a 53% CaO compound higher than Lake Toba, 51%. The content of Bilih Lake Toba fish muscle has P2O5 compounds 34,48% higher than Lake Singkarak with P2O5 34.58% higher, Bilih Danau Toba fish bone has CaO 57.66%, from Lake Singkarak 60,83%. Bilih Lake Toba has 97.32% Fluoride compound, higher than Lake Singkarak 98.43%. The ecological conditions in Lake Toba are relatively similar to the condition of the waters in Lake Singkarak.